DIAGNOSTIC ACCURACY OF CONTRAST–ENHANCED HIGHRESOLUTION MAGNETIC RESONANCE IMAGING (MRI) FORTHE DETECTION OF RETINOBLASTOMA - Muhammad Faisal (Baqai Journal of Health Sciences)
Objective To determine the diagnostic accuracy of contrast–enhanced high resolution magnetic resonance imaging (MRI) in the detection of retinoblastoma taking histopathology as the gold standard. Methodology A total of 50 cases were collected in this comparative cross-sectional study. The sample was taken through non-probability consecutive sampling. The study was conducted at Department of Radiology at Dr. Ziauddin Hospital, Karachi from 2011 to 2013. MRI orbit (Brain), using MRI field strength 1.5-T system head coil combined with one or two small surface coils. Results A total of fifty patients were enrolled with mean age 19.2±4.69 months with range (9-34) months. Gender distribution shows, 27 patients (54%) were male while remaining 23 patients (46%) were female. True positive cases were 34 (68%) and false positive cases were 3 (6%). Positive predictive value was 91.89%, negative predictive value 92.31% and the Diagnostic accuracy was found to be 92%. Conclusion In conclusion, the results of this study suggest that MR imaging proved to have a high diagnostic accuracy as well as positive predictive value in the detection of retinoblastoma taking histopathology as the gold standard. However, MRI is better in determining the extent of the disease and its complications.